(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda is eternal and continuous flow of ancient medicine, Now a day, Pratishyaya (Allergic rhinitis) is one of the most prevalent and common ailments. It is an atopic disease. Atopic is defined as familial tendency to sensitization to environment allergens (pollen, dust etc). It is a benign but chronic disease of upper airways and over all prevalence in round about 18% in general population. In Ayurveda, concept of allergy is scientifically explained under the Asatmayaj Vyadhi while its effects are explained in hereditary, Virudhahara, Dushivish and Ritusandhi. It is recurrent frequently and attending Jeerna avastha, Nasya is the line of treatment. In present time medical fraternity is attracted towards Nasya. It is a part of Panchakarma and is believed to be all round. The Present study tested efficacy of Pathaadi taila Nasya in the management of Pratishyaya w.s.r allergic rhinitis. The study was conducted on 15 patients, duration of 60 days. Total four sitting of Nasya Karma had done after having 7 days interval. After 14 days follow up the effect of Pathaadi tail Nasya assessed statistically based on the assessment criteria. It was observed that 14 days of Nasya karma decrease Pratishyaya, In this study we found that Pathaadi taila Nasya was effective in Pratishyaya.